187k views
0 votes
?????????????????????????

?????????????????????????-example-1
User Jens Alfke
by
5.2k points

1 Answer

4 votes

Answer:


\boxed{D. \: (f-g)(x) = {x}^(2) + 4x + 3}

Given:


f(x) =2 {x}^(2) - 5 \\ g(x) = {x}^(2) - 4x - 8

To find:


(f - g)(x) = f(x) - g(x)

Explanation:


\implies(f - g)x = f(x) - g(x) \\ \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = (2 {x}^(2) - 5) - ( {x}^(2) - 4x - 8) \\ \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = (2 {x}^(2) - 5) + (- {x}^(2) + 4x + 8) \\ \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = 2 {x}^(2) - 5 - {x}^(2) + 4x + 8 \\ \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = 2 {x}^(2) - {x}^(2) + 4x - 5 + 8 \\ \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = {x}^(2) + 4x + 8 - 5 \\ \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = {x}^(2) + 4x + 3

User VNT
by
5.5k points